Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1103/physrevlett.105.170401
|View full text |Cite
|
Sign up to set email alerts
|

PolarizedHe3as a Probe for Short-Range Spin-Dependent Interactions

Abstract: We have studied the relaxation of a spin-polarized gas in a magnetic field, in the presence of short-range spin-dependent interactions. As a main result we have established a link between the specific properties of the interaction and the dependence of the spin-relaxation rate on the magnitude of the holding magnetic field. This allows us to formulate a new, extremely sensitive method to study (pseudo) magnetic properties at the submillimeter scale, which are difficult to access by other means. The method has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
125
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 26 publications
(51 reference statements)
6
125
0
Order By: Relevance
“…Despite this difficulty, our analysis results in constraints that are within two orders of magnitude of hadronic axion models. This is sig-nificantly closer than limits on monopole-dipole couplings come to constraining QCD axions [23][24][25][26]. Furthermore, axion mediated dipole-dipole coupling scales as 1/f 4 a , (f a is the Peccei-Quinn symmetry breaking parameter) independent of the QCD θ parameter.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Despite this difficulty, our analysis results in constraints that are within two orders of magnitude of hadronic axion models. This is sig-nificantly closer than limits on monopole-dipole couplings come to constraining QCD axions [23][24][25][26]. Furthermore, axion mediated dipole-dipole coupling scales as 1/f 4 a , (f a is the Peccei-Quinn symmetry breaking parameter) independent of the QCD θ parameter.…”
mentioning
confidence: 90%
“…Constraints on new pseudoscalar interactions can also be obtained from spin-independent tests of the inverse square law [22]. Other laboratory experiments constrain anomalous monopole-dipole couplings on length scales in the range of µm to mm [23][24][25][26]. Spin relaxation studies of hyperpolarized 3 He gas have been used to limit anomalous dipole-dipole interactions between neutrons at length scales of about 100 nm [27].…”
mentioning
confidence: 99%
“…A similar analysis has been performed for other polarized species: Pokotilovski [13] set a limit using the measured Γ 1 of optically polarized noble gas. The use of polarized gases to study the monopole-dipole interaction can be found also in other recent works [20,21].…”
mentioning
confidence: 96%
“…Blue, from Ref. [21], by using low density 3 He gas. the contributions to Γ 2 from external magnetic field gradients and the gradient in the monopole-dipole field from nearby unpolarized objects including the test mass discussed above, we can identify several other contributions to Γ 2 [22,25] which we list here along with a qualitative discussion of their possible effect on our proposed search.…”
Section: Systematic Effectsmentioning
confidence: 99%
“…The detection of spin-dependent interactions, therefore, will enable to distinguish the axion from the scalar boson [15]. The static spin-dependent interactions have been carefully investigated for polarized electrons: experiments with a torsion pendulum [16][17][18][19][20][21] and paramagnetic salt [22][23][24] and for nucleons: measurements of precession frequency of atomic gases [25][26][27][28][29]; experiments with an ion trap [30] and neutron bound states [31,32]; spinrelaxation measurements of polarized particles [33][34][35][36]. On the other hand, the experimental constraints on the interactions dependent on both spins and the relative velocity are very few.…”
mentioning
confidence: 99%